ANALISIS KINERJA SAHAM LQ45 SEBELUM DAN SELAMA PANDEMI CORONAVIRUS DISEASE (COVID-19) DI INDONESIA - Martini Martini; Henry Anggoro Djohan (LPPM UNIVERSITAS BINA INSAN, 2020)
This study analyzes the performance of LQ45 shares before and during the Covid-19 pandemic in Indonesia. This study uses the monthly LQ45 stock price on the Indonesia Stock Exchange. The analysis uses two different conditions, before and during Covid-19 pandemic condition in Indonesia to see differences in conditions with a quantitative approach by emphasizing hypothesis testing. This research uses comparative causal research techniques. The results explained there were significant differences in the performance of LQ45 shares before and during the Covid-19 Pandemic in companies listed on the Indonesia Stock Exchange. The t-value from the results of the data processing analysis is 3.009 with sig. 0.004, it can be concluded that H(a) is accepted and H(0) is rejected. The performance of LQ45 shares on the Indonesian stock exchange experienced a decline during the pandemic that occurred in Indonesia. This situation caused many companies to suffer losses.